THE EFFECTIVENESS OF ORAL SUCROSE ON PAIN DURING INVASIVE PROCEDURES IN PREMATURE INFANTS: SCOPING REVIEW (STIKes Mitra Keluarga, 2021)
Introduction: Nowadays premature births continue to be common, it caused the infant necessitating treatment. Invasive procedures, such as the placement of an peripheral intravenous catheters or the drawing of blood, should be carried out while the baby is being cared for. Some intervention needed, sucrose is one approach to make invasive procedure less painful. This study aims to determine the effectiveness of oral sucrose in reducing the pain of invasive procedures in premature infants. Method: This study is a scoping review, and 11 articles were selected from Proquest, ScienceDirect, Willy Online, PubMed, and EBSCO (CINAHL) databases. Results: In eight of the articles, giving oral sucrose two minutes before the invasive procedure was effective in reducing pain, while sucrose was not effective in reducing pain in infants in the other three of the articles, during or after procedures. Conclusion: According to these studies, giving oral sucrose to premature infant before invasive procedure is significant reducing the pain during invasive procedure.